Activation and promotion of adipose stem cells by tumour necrosis factor‐alpha preconditioning for bone regeneration. Issue 8 (18th April 2013) - Lu, ZuFu; Wang, GuoCheng; Dunstan, Colin R.; Chen, YongJun; Yenn‐Ru Lu, William; Davies, Ben; Zreiqat, Hala
Abstract There is a major medical need for developing novel and effective approaches for repairing non‐union and critical‐sized bone defects. Although the mechanisms remain to be determined, it is known that inflammation plays a crucial role in initiating bone repair and regeneration. This study investigated the effect of short‐term (3 days) preconditioning with tumor necrosis factor‐alpha (TNF‐α) on proliferation, mobilization, and differentiation of adipose tissue‐derived mesenchymal stem cells (ASCs). We demonstrated that TNF‐α pre‐conditioning increased proliferation, mobilization, and osteogenic differentiation of ASCs and up‐regulated bone morphogenetic protein‐2 (BMP‐2) protein level. BMP‐2 silencing by siRNA partially inhibited osteogenic differentiation of ASCs induced by TNF‐α; BMP‐2 pre‐conditioning also significantly increased osteogenic differentiation of ASCs but the effects were significantly smaller than those observed for TNF‐α preconditioning. Furthermore, TNF‐α treatment promoted extracellular‐signal‐regulated kinases(Erk)1/2 and p38 mitogen‐activated protein kinase (MAPK) signaling pathways, but only Erk1/2 inhibition reduced the BMP‐2 levels and osteogenic differentiation induced by TNF‐α preconditioning. Together, these results support the hypothesis that inflammation contributes to bone regeneration by promoting proliferation, mobilization, and osteogenic differentiation of ASCs; 3 days of TNF‐α preconditioning, mimicking the short boost of inflammation normally occurring after bone injury, might serve as a feasible approach for directing stem cells into osteogenic differentiation. J. Cell. Physiol. 9999: XX–XX, 2013. © 2013 Wiley Periodicals, Inc. J. Cell. Physiol. 228: 1737–1744, 2013. © 2013 Wiley Periodicals, Inc.